(untitled) (European Journal of Health Research, 2021)
Pleural fibrous tumor is a rare medical entity, considered a benign tumor. It accounts for 5-8% of primary pleura tumors. We report the case of a 59-year-old, non-smoking male patient with a 3-month history of liquid bowel movements, associated with asthenia, weight loss and costal grill pain. He was admitted to the Gastroenterology Service of the Hermanos Ameijeiras Surgical Clinical Hospital, Havana, Cuba. He was given a chest x-ray, observing as an accidental finding a tumor mass in the cardiac region, so he decides to interconsult with the Pneumology service. Chest tomography showed tumor mass in the lower third of left hemitórax, the histological and immunohistochemical study was compatible with a pleural solitary fibrous tumor. Conclusions of this work suggest that for the precise diagnosis of this type of tumor it is necessary to perform a chest axial tomography and a detailed histopathological analysis.